Consumer motivations and barriers towards purchase of local beef - Bernard, Sarah (Kansas State University, 2012)
This research focuses on factors that serve as motivators or as barriers for consumers in their purchase of local beef. To understand the purchasing habits and preferences of the consumer, a designed survey was used. A convenience population was recruited and encouraged to participate in the survey online. Supporting local agriculture was found to be the highest motivating factor for purchase of local beef within the survey population. That was followed by taste, environment, humane treatment, and health benefits, in that order. Women agreed to all motivating factors at a statistically significantly rate greater than their male counterparts. Price was found to be the largest barrier to the purchase of local beef among the respondents. Lesser barriers were appeal of specifics, convenience, unfamiliar brand, and quality. Statistically significant differences were noted between respondents who had actually purchased local beef versus those that would consider such purchase. Respondents with prior purchasing experience did not perceive the listed barriers to be as inhibitory to their purchase as those who had no prior buying experience. Recommendations produced from this research encourage farmer groups and individual farms to focus on their customer characteristics through key motivating factors, women, and those supporting local agriculture. Finding ways to encourage consumers to try local beef should combat barriers to purchase. Farmers markets should create an experience that customers want to come to and enjoy and individual producers should be relatable and available to customers. Future research could include a large, randomized population of respondents that could give a more accurate description of the typical American consumer with opportunity to expand into other motivating or barrier influences. Other ideas for research could include other motivating and barrier factors, as well as open ended questions and focus groups to gain further insights into the consumer mind with regard to local beef.
Keywords: Local; Locavore; Beef; Motivations; Barriers; Consumer behavior; Business Education (0688); Marketing (0338); Psychology (0621)